A method for preparing porous polymer and its application in the treatment of high-salt, high-ammonia and high-nitrogen wastewater and metal wastewater
By using 1,3,5-benzene tripinacol ester and bis(sodium hydroxypropanesulfonate bromobenzene)catechol monomers for coupling polymerization, porous materials with high specific surface area and rich pore structure were prepared. The polymer solves the problem of poor performance of existing porous organic polymers in ammonia nitrogen wastewater treatment and achieves efficient adsorption of ammonia nitrogen and metal ions.
Patent Information
- Application Number
- CN202410544068.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-06
AI Technical Summary
The existing porous organic polymers are not effective in the treatment of ammonia nitrogen wastewater, and it is difficult to effectively adsorb ammonia nitrogen and metal ion pollutants.
By using 1,3,5-benzene tripinacol ester and novel bis(sodium hydroxypropanesulfonate bromobenzene)catechol monomer for coupling polymerization, a high specific surface area and rich pore structure were prepared. Porous polymers. The molecular backbone of the porous polymer contains sulfonate, hydroxyl groups and catechol structures, which can produce strong coordination and chelation with metal ions and ammonia nitrogen.
The prepared porous polymer shows efficient adsorption performance in the treatment of high-salt, high-ammonia-nitrogen wastewater and metal wastewater. The removal rate of metal ions such as Pd2+ and Hg2+ reaches 95.9-99.8% and 94.0-99.5%, and the removal rate of ammonia nitrogen Reaching 87.2-92.7%, significantly improving the effect of wastewater treatment.
Smart Images

Figure CN118440300B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, in particular to a method for preparing a porous polymer and its application in the treatment of high-salt, high-ammonia nitrogen wastewater and metal wastewater. Background Art
[0002] In industry, agriculture, and people's daily life, a large amount of sewage and wastewater is generated, which contains a large amount of pollutants such as ammonia nitrogen, organic matter, heavy metal ions, inorganic salts, etc. The efficient treatment of these sewage and wastewater is imminent. At present, the main treatment methods are precipitation method, microbial degradation method, adsorption method, etc. Among them, the adsorption method is simple to operate, low in cost, and has a variety of adsorption materials. It is the most widely used in the treatment of wastewater such as ammonia nitrogen and metals. It is of great significance to develop adsorption materials with multiple adsorption sites and strong adsorption performance.
[0003] Porous polymer materials have a high specific surface area and a large number of adsorption sites, and have broad application prospects in the fields of gas adsorption and wastewater treatment. China CN113896849B discloses a thioether-functionalized porphyrin structure porous organic polymer and its preparation method and application in the adsorption of heavy metals in water. The thioether-functionalized terephthalaldehyde monomer and pyrrole monomer are subjected to porphyrin polycondensation reaction to obtain a thioether-functionalized porphyrin structure porous organic polymer. 2+ , Cu 2+ and Hg 2+ etc. have a selective absorption effect, but the porous organic polymer does not show an adsorption effect on ammonia nitrogen and has no good practical application in ammonia nitrogen wastewater treatment. Summary of the invention
[0004] The invention provides a porous polymer capable of efficiently adsorbing ammonia nitrogen and metal ion pollutants.
[0005] The technical solution provided by the present invention is:
[0006] A method for preparing a porous polymer: adding N,N-dimethylformamide, 1,3,5-benzenetriboric acid tripinacol ester, and a structural formula Bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer, tetrakis(triphenylphosphine)palladium, potassium carbonate and distilled water solvent are stirred at 80-100°C for 48-72h, filtered while hot, washed with distilled water, ethanol and toluene in turn, and dried to obtain a porous polymer.
[0007] Furthermore, the ratio of 1,3,5-benzenetriboric acid tripinacol ester, bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer, tetrakis(triphenylphosphine)palladium, and potassium carbonate is 1 mol:(1.3-1.7) mol:(0.048-0.054) mol:(1.6-2) mol.
[0008] Furthermore, the ratio of N,N-dimethylformamide to distilled water solvent is 1L:(0.1-0.15)L.
[0009] Further, the preparation method of bis(sodium bromobenzene hydroxypropanesulfonate)catechol monomer is as follows:
[0010] Step S1, add ethanol, 2,3-dihydroxyterephthalaldehyde and 4-bromoaniline to a reaction bottle, stir and react at 60-75° C. for 8-12 hours, then cool to room temperature, add sodium borohydride, stir and react for 3-5 hours, then concentrate to remove ethanol, add distilled water and ethyl acetate, shake, stand and separate, extract and take the organic layer, concentrate, and dry to obtain a bis(iminobromobenzene)catechol intermediate.
[0011] Step S2, add ethanol, 1 mol:(2.4-3) mol:(2.4-3.2) mol of bis(iminobromobenzene)catechol intermediate, sodium 3-chloro-2-hydroxypropanesulfonate, sodium hydroxide, and distilled water to a reaction bottle, stir and react at 45-70° C. for 12-18 hours, add dilute hydrochloric acid to adjust the pH of the solution to neutral after cooling, concentrate to remove ethanol, add saturated sodium chloride solution and ethyl acetate, shake, stand to separate, extract and take the organic layer, concentrate, and dry to obtain bis(sodium bromobenzene hydroxypropanesulfonate)catechol monomer.
[0012] Furthermore, in step S1, the ratio of 2,3-dihydroxyterephthalaldehyde, 4-bromoaniline and sodium borohydride is 1 mol:(2-2.4) mol:(2.6-3.2) mol.
[0013] Furthermore, porous polymers are used in the treatment of high-salt, high-ammonia-nitrogen wastewater and metal wastewater.
[0014] The technical effect of the present invention is as follows: the present invention utilizes 1,3,5-benzenetriboric acid tripinacol ester and novel bis(sodium bromophenyl hydroxypropanesulfonate) catechol monomer for coupling polymerization reaction, and the specific surface area of the obtained porous polymer reaches 863.5-984.9m2 / g, and the total pore volume reaches 0.403-0.454m 3 / g. It has a rich pore structure and a high specific surface area, which is beneficial to increase adsorption sites and improve adsorption performance.
[0015] The molecular backbone of the porous polymer of the present invention contains a large amount of sulfonate, hydroxyl groups, and catechol structures, which can react with Pd 2+ , Hg 2+ The coordination and chelation of metal ions, especially the catechol structure, has stronger coordination ability, which significantly improves the chelation of porous polymers to Pd 2+ , Hg 2+ The adsorption performance of Pd 2+The removal rate of Hg 2+ The removal rate reaches 94.0-99.5%. It has broad application prospects in the treatment of metal-containing wastewater.
[0016] The porous polymer of the present invention contains a large number of sulfonate groups, which can generate a large number of sulfonate anions by hydrolysis, and can react with NH4 + Electrostatic interaction occurs, which has a good adsorption effect. When the ammonia nitrogen solution is of low mass concentration (20mg / L), the removal rate of ammonia nitrogen reaches 87.2-92.7%. When the ammonia nitrogen solution is of high mass concentration (100-500mg / L), it also shows a high ammonia nitrogen removal rate. It has good practical application in the treatment of high-concentration ammonia nitrogen wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a reaction route for preparing bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer.
[0018] Figure 2 It is the reaction mechanism for preparing porous polymers.
[0019] Figure 3 This is a scanning electron microscope image of a porous polymer. DETAILED DESCRIPTION
[0020] The following will describe the implementation methods of the present invention in detail in conjunction with specific embodiments, so that the implementation process of how the present invention applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0021] Example 1
[0022] Step S1, add 50mL ethanol, 30mmol 2,3-dihydroxyterephthalaldehyde, 72mmol 4-bromoaniline to the reaction bottle, stir and react at 60°C for 12h, then cool to room temperature, add 78mmol sodium borohydride, stir and react for 5h, then concentrate to remove ethanol, add distilled water and ethyl acetate, shake, stand and separate, extract and take the organic layer, concentrate, and dry to obtain bis(iminobromophenyl)catechol intermediate. Theoretical yield 30mmol, 14.28g, actual yield 8.01g, yield 56.09%.
[0023] Step S2, add 120mL ethanol, 30mmol bis(imino bromobenzene)catechol intermediate, 72mmol 3-chloro-2-hydroxypropanesulfonate sodium, 72mmol sodium hydroxide, and add 20mL distilled water to the reaction bottle, stir and react at 70°C for 12h, add dilute hydrochloric acid to adjust the pH of the solution to neutral after cooling, concentrate to remove ethanol, add saturated sodium chloride solution and ethyl acetate, shake, stand and stratify, extract and take the organic layer, concentrate, and dry to obtain bis(sodium bromobenzene hydroxypropanesulfonate)catechol monomer. Theoretical yield 30mmol, 23.88g, actual yield 14.58g, yield 61.06%.
[0024] Example 2
[0025] Step S1, add 30mL ethanol, 30mmol 2,3-dihydroxyterephthalaldehyde, 60mmol 4-bromoaniline to the reaction bottle, stir and react at 70°C for 8h, then cool to room temperature, add 96mmol sodium borohydride, stir and react for 3h, then concentrate to remove ethanol, add distilled water and ethyl acetate, shake, stand and separate, extract and take the organic layer, concentrate, and dry to obtain bis(iminobromobenzene)catechol intermediate. Theoretical yield 30mmol, 14.28g, actual yield 8.63g, yield 60.43%.
[0026] Step S2, add 140mL ethanol, 30mmol bis(imino bromobenzene)catechol intermediate, 90mmol 3-chloro-2-hydroxypropanesulfonate sodium, 96mmol sodium hydroxide, and add 30mL distilled water to the reaction bottle, stir and react at 45°C for 18h, add dilute hydrochloric acid to adjust the pH of the solution to neutral after cooling, concentrate to remove ethanol, add saturated sodium chloride solution and ethyl acetate, shake, stand and decompose, extract and take the organic layer, concentrate, and dry to obtain bis(sodium bromobenzene hydroxypropanesulfonate)catechol monomer. Theoretical yield 30mmol, 23.88g, actual yield 17.25g, yield 72.23%.
[0027] Example 3
[0028] Add 500 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-benzenetriboric acid tripinacol ester, 65 mmol of bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer (prepared in the same manner as in Example 1), 2.4 mmol of tetrakis(triphenylphosphine)palladium, 80 mmol of potassium carbonate and 50 mL of distilled water solvent into a reaction bottle, stir and react at 85° C. for 60 h, filter while hot, wash with distilled water, ethanol and toluene in turn, and dry to obtain a porous polymer.
[0029] Example 4
[0030] 500 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-benzenetriboric acid tripinacol ester, 75 mmol of bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer (prepared in the same manner as in Example 1), 2.7 mmol of tetrakis(triphenylphosphine)palladium, 100 mmol of potassium carbonate and 75 mL of distilled water solvent were added to a reaction bottle, and the mixture was stirred at 80° C. for 72 h, filtered while hot, washed with distilled water, ethanol and toluene in sequence, and dried to obtain a porous polymer.
[0031] Example 5
[0032] Add 500 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-benzenetriboric acid tripinacol ester, 85 mmol of bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer (prepared in the same manner as in Example 1), 2.7 mmol of tetrakis(triphenylphosphine)palladium, 90 mmol of potassium carbonate and 75 mL of distilled water solvent into a reaction bottle, stir and react at 100° C. for 48 h, filter while hot, wash with distilled water, ethanol and toluene in turn, and dry to obtain a porous polymer.
[0033] Comparative Example 1
[0034] Add 500 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-benzenetriboric acid tripinacol ester, 65 mmol of bis(iminobromobenzene)catechol intermediate (prepared in the same manner as in Example 1), 2.4 mmol of tetrakis(triphenylphosphine)palladium, 80 mmol of potassium carbonate and 50 mL of distilled water solvent into a reaction bottle, stir and react at 85° C. for 60 h, filter while hot, wash with distilled water, ethanol and toluene in turn, and dry to obtain a porous polymer.
[0035] The specific surface area and total pore volume of the porous polymer were tested using a pore size distribution analyzer at a test temperature of 77 K and a nitrogen atmosphere.
[0036] Table 1 Specific surface area and total pore volume test of porous polymers
[0037]
[0038]
[0039] Prepare 500mL of Pd with a mass concentration of 20mg / L (denoted as C0) 2+ The solution was adjusted to pH 6, and then 150 mg of porous polymer was added, stirred and dispersed, and then oscillated and adsorbed at room temperature for 1-3 hours. After adsorption, the supernatant was taken and Pd was determined by atomic absorption spectrophotometer. 2+ The concentration (denoted as C) is used to calculate the removal rate W. W = (C0-C) / C0×100%.
[0040] Table 2 Porous polymer adsorption of Pd 2+ Performance Testing
[0041]
[0042] Prepare 500mL of Hg with a mass concentration of 20mg / L (denoted as C0) 2+ The solution was adjusted to pH 6, and then 200 mg of porous polymer was added, stirred and dispersed, and then oscillated and adsorbed at room temperature for 1-4 h. After adsorption, the supernatant was taken and Hg was determined by atomic absorption spectrophotometer. 2+ The concentration (denoted as C) is used to calculate the removal rate W. W = (C0-C) / C0×100%.
[0043] Table 3 Porous polymer adsorption of Hg 2+ Performance Testing
[0044]
[0045]
[0046] Prepare 1000mL of ammonium chloride aqueous solution, control the mass concentration of ammonia nitrogen in the solution to 20-500mg / L (denoted as C0), then add 0.2-5g of porous polymer, oscillate and adsorb for 4h at room temperature, and use Nessler's reagent spectrophotometry to determine the mass concentration of ammonia nitrogen in the solution after adsorption (denoted as C). Calculate the removal rate W. W = (C0-C) / C0×100%.
[0047] The specific surface area of the porous polymers of Examples 1-3 reached 863.5-984.9 m2 / g, and the total pore volume reached 0.403-0.454 m 3 / g. It has a rich pore structure and a high specific surface area, which is beneficial to increase the adsorption sites and improve the adsorption performance. When the adsorption time is 3h, the adsorption of Pd 2+ The removal rate of Hg 2+ The removal rate reaches 94.0-99.5%. This is because the main chain of the porous polymer contains a large number of sulfonates, hydroxyl groups, and catechol structures, which can react with Pd 2+ , Hg 2+ The coordination and chelation of metal ions, especially the catechol structure, has stronger coordination ability, which significantly improves the chelation of porous polymers to Pd 2+ , Hg 2+ The adsorption performance showed a high removal rate.
[0048] Comparative Example 1: 1,3,5-benzenetriboric acid tripinacol ester, bis(iminobromophenyl)catechol intermediate As a polymerization monomer, the prepared porous polymer has a large specific surface area and total pore volume, many adsorption sites, and also contains catechol structure, which can react with Pd 2+ , Hg 2+ However, the porous polymer does not contain sulfonic acid groups, and the hydroxyl content is less than that of Examples 3-5, resulting in the porous polymer being unable to react with Pd 2+ , Hg 2+ The removal rate is lower than that of Example 3-5.
[0049] Table 4 Porous polymer adsorption performance test of ammonia nitrogen
[0050]
[0051]
[0052] The porous polymer of Example 3-5 contains a large number of sulfonate groups, which can generate a large number of sulfonate anions by hydrolysis, and can react with NH4 + Electrostatic interaction occurs, which has a good adsorption effect. When the ammonia nitrogen solution is of low mass concentration (20mg / L), the removal rate of ammonia nitrogen reaches 87.2-92.7%. When the ammonia nitrogen solution is of high mass concentration (100-500mg / L), it also shows a high ammonia nitrogen removal rate. It has good practical application in the treatment of high-concentration ammonia nitrogen wastewater.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a porous polymer, characterized in that: The preparation method is as follows: add N,N-dimethylformamide, 1,3,5-benzenetriboric acid tripinacol ester, bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer, tetrakis(triphenylphosphine)palladium, potassium carbonate and distilled water solvent into a reaction bottle, stir and react at 80-100° C. for 48-72 hours, filter while hot, wash and dry to obtain a porous polymer; The structural formula of the bis(sodium bromobenzene hydroxypropanesulfonate)catechol monomer is as follows: ; The ratio of the 1,3,5-benzenetriboric acid tripinacol ester, bis(sodium bromophenyl hydroxypropanesulfonate)catechol monomer, tetrakis(triphenylphosphine)palladium and potassium carbonate is 1 mol:(1.3-1.7) mol:(0.048-0.054) mol:(1.6-2) mol.
2. The method for preparing a porous polymer according to claim 1, characterized in that: The ratio of the N,N-dimethylformamide to the distilled water solvent is 1L:(0.1-0.15)L.
3. The method for preparing a porous polymer according to claim 1, characterized in that: The preparation method of the bis(sodium bromobenzene hydroxypropanesulfonate)catechol monomer is as follows: Step S1, adding ethanol, 2,3-dihydroxyterephthalaldehyde and 4-bromoaniline to a reaction bottle, stirring and reacting at 60-75° C. for 8-12 hours, then cooling to room temperature, adding sodium borohydride, stirring and reacting for 3-5 hours, then concentrating to remove ethanol, extracting, concentrating and drying to obtain a bis(iminobromobenzene)catechol intermediate; Step S2, adding ethanol, bis(iminobromobenzene)catechol intermediate, sodium 3-chloro-2-hydroxypropanesulfonate, sodium hydroxide, and distilled water into a reaction bottle, stirring for reaction, adding dilute hydrochloric acid to adjust the pH of the solution to neutral, concentrating to remove ethanol, extracting, concentrating, and drying to obtain bis(sodium bromobenzene hydroxypropanesulfonate)catechol monomer.
4. The method for preparing a porous polymer according to claim 3, characterized in that: In the step S1, the ratio of 2,3-dihydroxyterephthalaldehyde, 4-bromoaniline and sodium borohydride is 1 mol: (2-2.4) mol: (2.6-3.2) mol.
5. The method for preparing a porous polymer according to claim 3, characterized in that: In the step S2, the ratio of the bis(iminobromobenzene)catechol intermediate, sodium 3-chloro-2-hydroxypropanesulfonate, and sodium hydroxide is 1 mol:(2.4-3) mol:(2.4-3.2) mol.
6. The method for preparing a porous polymer according to claim 3, characterized in that: In the step S2, the reaction is carried out at 45-70° C. for 12-18 hours.
7. Use of the porous polymer obtained by the preparation method according to any one of claims 1 to 6 in the treatment of high-salt and high-ammonia nitrogen wastewater and metal wastewater.
Citation Information
Patent Citations
A thioether-functionalized porphyrin-structured porous organic polymer, its preparation method, and its application in adsorbing heavy metals in water.
CN113896849B
Nitrogen-sulfur-boron co-doped carbon aerogel-based sulfur composite material, preparation method and application thereof
CN113471416A
Porphyrin type conjugated microporous polymer as well as synthesis method and application thereof
CN113698579A